Top exporters and regional export specialization - Juan De Lucio; Raúl Mínguez; Asier Minondo; Francisco Requena (National Accounting Review)
We examined the role of top exporters in sub-national export specialization using Spanish firm-level export data at the province (NUTS 3) level. Our results show that, on average, 28% of aggregate exports in each province are in sectors where the top exporter determines the revealed comparative advantage (RCA). Moreover, provinces with sectors where the top exporter determines the RCA exhibit a more unstable pattern of export specialization over time. This result suggests that the characteristics and strategies of large firms may affect regional specialization patterns.